HUBUNGAN KEMANDIRIAN BELAJAR DENGAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V MI MUHAMMADIYAH 2 SINGKAWANG - Moch Ahsanul Romadhoni; Rien Anitra; Gunta Wirawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to: 1) Describe the students' reading comprehension ability seen from the learning independence in class V MI Muhammadiyah 2 Singkawang. 2) Describe the learning independence of class V students of MI Muhammadiyah 2 Singkawang which is still low. 3) Describe the relationship between learning independence and the reading comprehension ability of class V students of MI Muhammadiyah 2 Singkawang. The type of research used is quantitative with a correlational research design. The population in this study were all class V students of MI. Muhammadiyah 2 Singkawang totaling 42 students. From this population, samples were taken using the total sampling technique, so that the sample used was 42 students. The data collection techniques used in this study were indirect communication techniques and measurement techniques, with questionnaire and test research instruments. The student independence questionnaire consisted of 22 statements and the reading comprehension ability test consisted of 10 multiple choice questions. The data analysis techniques used were percentage and correlation. The data analysis technique used the Pearson product moment correlation formula with a significance level of 5% (0.05). The results of the study showed that 1) the level of student learning independence was classified as high with an average value of 77, 2) the level of student reading comprehension ability was classified as high with an overall average value of 79, 3) there was a significant relationship (correlation) between learning independence and reading comprehension ability. With a correlation coefficient of 0.41 (categorized as moderate) which means that learning independence plays a role in influencing reading comprehension ability with a contribution of 25%. From the results of the research that has been conducted, there is a relationship between learning independence and reading comprehension ability.